Sensitive reading : the pleasures of South Asian literature in translation - Bronner, Yigal; Hallisey, Charles, 1953-; Shulman, David Dean, 1949- (University of California Press, 2021)
"What are the pleasures of reading translations of South Asian literature and what does it take to enjoy them? This volume explores these questions by bringing together a whole set of new translations by David Shulman, noted scholar of South Asia. The translated selections come from a variety of Indian languages, genres, and periods, from classical to current. They are accompanied by short essays especially written to help readers engage and enjoy them. Some of these essays provide background to enhance any reading of the translation while others model how to expand appreciation in broader and comparative ways. Taken together, the translations and the accompanying essays form an essential guide for people interested in literature and art from South Asia"--